Tail Distribution Estimates of Fractional CIR Model - Hang, Nguyen Thu; Tan, Nguyen Van (VNU Journal of Science: Mathematics - Physics, 2022)
The aim of this work is to study the tail distribution of the Cox–Ingersoll–Ross (CIR) model driven by fractional Brownian motion. We first prove the existence and uniqueness of the solution. Then based on the techniques of Malliavin calculus and a result established recently in [1], we obtain an explicit estimate for tail distributions.